2015
DOI: 10.1111/jfb.12653
|View full text |Cite
|
Sign up to set email alerts
|

Using biological variables and reproductive strategy of the undulate ray Raja undulata to evaluate productivity and susceptibility to exploitation

Abstract: The present work provides a detailed analysis of the reproductive strategy of the undulate ray Raja undulata in Portuguese mainland waters. The species was found mostly between 30 and 40 m deep on sandy bottoms. Egg-laying sites were observed in the north, centre and south-west regions, mainly at depths below 30 m. The peak of the reproductive season occurred from December to May. Asynchrony between reproductively active females and males appeared to occur, although most adult males were capable of reproducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The nature of the relationship between maternal size and the number or size of vitellogenic oocytes in oviparous elasmobranchs appears to be species specific. Some studies have reported no significant effect of maternal size on reproductive output (Perez-Brazen et al, 2014;Serra-Pereira et al, 2015), while others have reported trends similar to those observed in B. parmifera (Ainsley et al, 2011;Haas, 2011). While these relationships tend to be weak and highly variable, they may be still be useful information for fisheries managers, potentially with extra protection afforded to larger, more productive females.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The nature of the relationship between maternal size and the number or size of vitellogenic oocytes in oviparous elasmobranchs appears to be species specific. Some studies have reported no significant effect of maternal size on reproductive output (Perez-Brazen et al, 2014;Serra-Pereira et al, 2015), while others have reported trends similar to those observed in B. parmifera (Ainsley et al, 2011;Haas, 2011). While these relationships tend to be weak and highly variable, they may be still be useful information for fisheries managers, potentially with extra protection afforded to larger, more productive females.…”
Section: Discussionmentioning
confidence: 87%
“…The nature of the relationship between maternal size and the number or size of vitellogenic oocytes in oviparous elasmobranchs appears to be species specific. Some studies have reported no significant effect of maternal size on reproductive output (Perez‐Brazen et al , ; Serra‐Pereira et al , ), while others have reported trends similar to those observed in B . parmifera (Ainsley et al , ; Haas, ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Ellis et al, 2012Ellis et al, , 2004Serra-Pereira et al, 2014;Walker et al, 1997). Reproduction of R. undulata is supposed to occur between winter and spring, with egg-laying occurring shortly after (Moura et al, 2007;Serra-Pereira et al, 2015). Whereas, the reproductive strategy for R. clavata and R. montagui is supposed to peak in summer (Koop, 2005;Serra-Pereira et al, 2011).…”
Section: Life History Trait Differences Demonstrating the Need For Spmentioning
confidence: 99%
“…The three skates were additionally divided according to two size classes: juveniles (<=25 cm; equation 7), and mature (>=80 cm for R. undulata, >=75 cm for R. clavata and >=65 cm for R. montagui; equations 8 to 10), to investigate potential essential skate habitat. The size classes were based upon density frequency plots and existing literature(Coelho and Erzini, 2006;Ellis et al, 2012;Koop, 2005;McCully et al, 2012;Serra-Pereira et al, 2015. Presence absence models by sex were also explored (equations 11 to 16).…”
mentioning
confidence: 99%